The morphology, clinical significance and imaging methods of the atrial septal pouch: A critical review - Małgorzata Mazur (Translational Research in Anatomy, 2018)
The purpose of this study was to present current knowledge about the atrial septal pouch, which is a relatively new anatomical discovery located within the human interatrial septum of the heart. The atrial septal pouch is formed during the postnatal partial fusion of the primary and secondary septum. The prevalence of the left septal pouch is 40.8%, the right septal pouch is present in 5.1% and a double pouch is seen in 3.7% of cases. The patent foramen ovale channel is present in 25.9% of all cases. The left septal pouch is a relatively small structure with an average depth of 8.4 ± 5.1 mm and mean volume of 0.31 ± 0.11 ml. The right septal pouch is significantly smaller than the left septal pouch, with a mean depth of 6.2 ± 3.4 mm and mean volume of 0.25 ± 0.08 ml. Both transesophageal echocardiography and cardiac computed tomography are useful techniques for detecting left septal pouches with the insignificant lower prevalence of detecting left septal pouches compared to the matched postmortem material. Transesophageal echocardiography with contrast modality seems to be superior than computed tomography due to its unambiguous patent foramen ovale channel detection and it should be the preferred imaging technique in clinical identification of septal pouches. The anatomy of left septal pouch may promote blood stasis and thrombus formation. Case reports and cross-sectional, single-center studies show that there is an association between the presence of a left sided septal pouch and an increased risk for cryptogenic stroke. Moreover, the left septal pouch may be an arrhythmogenic substrate responsible for triggering atrial fibrillation. The right septal pouch seems to have no clinical significance. In summary, the left septal pouch is the most common structure found within the interatrial septum and should be considered as a normal variant of the human heart anatomy. The morphological nature of the atrial septal pouch is well known, however, more clinical research is needed to resolve its possible connection with atrial fibrillation and cardio-embolic stroke. Keywords: Interatrial septum, Atrium, Ischemic stroke, Cardioembolic stroke, Patent foramen ovale, Atrial fibrillation, Thrombosis